Shelf life determination of frozen bread dough stored under fluctuating temperature conditions - Yuthana Phimolsiripol (2018)
The shelf life of frozen bread dough stored under both constant and fluctuating temperature conditions was investigated. Storage regimes were designed to mimic either good or poor practice likely to be experienced in the cold chain (-18 ± 0.1°C, -18 ± 1°C, -18 ± 3°C or -18 ± 5°C). Gas production, dough water mobility and bread crumb characteristics were measured as quality parameters. The acceptability of bread made from frozen dough was monitored using a modified Weibull hazard sensory method. The shelf life results were considered from a kinetic standpoint with a focus on the effect of temperature on the acceleration of deterioration. Temperature fluctuations during storage accelerated deterioration in frozen bread dough. Large temperature fluctuations (-18 ± 5°C) and storage at higher temperatures (a combination of -18°C, -13°C and -8°C) during frozen storage resulted in significantly more rapid loss of dough and bread quality than storage at constant temperatures. A broken (nuclear magnetic resonance) peak of frozen dough stored under large temperature changes indicated greater separation of water bound to the starch-gluten matrix. The shelf life of frozen dough stored under large temperature fluctuations and higher temperatures was about 12 weeks, whereas the shelf life of the dough stored under constant or less fluctuating temperatures was greater than 16 weeks.